2012
DOI: 10.1186/1471-2393-12-44
|View full text |Cite
|
Sign up to set email alerts
|

A population-based investigation into inequalities amongst Indigenous mothers and newborns by place of residence in the Northern territory, Australia

Abstract: Background Comparisons of birth outcomes between Australian Indigenous and non-Indigenous populations show marked inequalities. These comparisons obscure Indigenous disparities. There is much variation in terms of culture, language, residence, and access to services amongst Australian Indigenous peoples. We examined outcomes by region and remoteness for Indigenous subgroups and explored data for communities to inform health service delivery and interventions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
0
39
0
1
Order By: Relevance
“…The rates are possibly the highest rates in Australia, 11 are also high by international standards, 1 and were higher than those reported in the general Darwin region (their sample had 76.7% of Aboriginal babies which included women from these communities) more than 20 years ago (liveborn singletons had PTB: 7.4% and LBW 13.9%). 31 Even though remoteness is a known independent risk factor for poorer outcomes in the NT and regional differences have been identified 12 this study highlights the importance of community/regional specific reporting to enable targeted strategies where they are needed most. When looking at socioeconomic disadvantage these communities are in the lowest 2% of all communities in Australia, thus it was not surprising that we found high rates of teenage mothers (28.3%).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The rates are possibly the highest rates in Australia, 11 are also high by international standards, 1 and were higher than those reported in the general Darwin region (their sample had 76.7% of Aboriginal babies which included women from these communities) more than 20 years ago (liveborn singletons had PTB: 7.4% and LBW 13.9%). 31 Even though remoteness is a known independent risk factor for poorer outcomes in the NT and regional differences have been identified 12 this study highlights the importance of community/regional specific reporting to enable targeted strategies where they are needed most. When looking at socioeconomic disadvantage these communities are in the lowest 2% of all communities in Australia, thus it was not surprising that we found high rates of teenage mothers (28.3%).…”
Section: Discussionmentioning
confidence: 88%
“…1,6,7,10 There is significant disparity between Aboriginal and nonAboriginal Australians for these outcomes: PTB (14.3% vs. 8.3%) and LBW (11.8% vs. 6.0%) 11 ; and the risk factors for example: teenage pregnancy (18.6% vs 3.0%), smoking in pregnancy (48.1% vs 10.7%) and living in remote areas (24.1% vs. 1.8%). 11,12 Aboriginal mothers are also more likely to attend antenatal care later in pregnancy and receive less antenatal visit than non-Aboriginal mothers. 4 A few Australian studies have reported risk factors for PTB and LBW among Aboriginal women from regional and urban areas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 In Australia, remoteness was found to be an independent factor in birth outcomes. 13 In France, greater distance was associated with worse outcomes. 14 In Wales, greater distance to hospital was associated with higher risk of neonatal mortality.…”
Section: Lettresmentioning
confidence: 99%